A Novel PRESH controller design for three phase grid tied SPPS - Uma Yadav (Elsevier, 2022)
The proposed paper presents the novelty of new type of controller for three phase grid tied SPPS. This new controller is credited with a name of “PRESH” helpful in mitigating the harmonic of three phase GTSPPS (Grid Tied Solar Photovoltaic Power System) even during abnormal grid condition. Presented Novel PRESH controller is formed by combining the characteristic of PRES and RESH Controller but is totally different from the already proposed controller of present days. Further, investigation of Novel PRESH controller is done in term of its harmonic mitigation technique with the help of both Bode-Plot and MATLAB Simulink. Presently, for eliminating the harmonic from three phase GTSPPS, various filters and controllers have already been proposed but it either resulted in increase of computational load or make the system bulky. Earlier technique develops in eliminating the harmonic face difficulty in eliminating the harmonic when the reference waveform gets distorted from its original position. The proposed Novel “PRESH” controller can also be incorporated when grid suffers from any abnormal condition. The proposed paper has also discussed the performance analysis of Novel PRESH controller along with its design procedure that are helpful in mitigating the THD of three phase SPPS near to 1% and thus satisfying the IEEE standard 519 and 1547.